Realizing Justice in Agricultural Practices in Islamic Law: A Study of Hybrid Contract in Gulo Onou Production - Rahmat, Aditya; Yunarti, Sri; Warman, Arifki Budia (JISRAH: Jurnal Integrasi Ilmu Syariah, 2024)
This study analyzes the practice of contracts and the distribution of income in the production of Gulo Onou in Nagari Batu Bulek from the perspective of fiqh muamalah. The study aims to answer the research questions regarding the practices of contracts and income distribution in the production of Gulo Onou in Nagari Batu Bulek and how fiqh muamalah analyzes these practices. Through field research with interviews, it was found that the cooperation between the owner of the Onou tree and the caretaker of the Onou tree met the conditions of the Musaqah contract. This includes the involvement of two parties—the owner of the Onou tree and the caretaker—an oral agreement, and the object of the contract, which is the Onou tree. The musaqah practice in question is a contract in which the landowner hands over the land to be managed by the caretaker. The income from the production of Gulo Onou is shared according to the mutually agreed terms, which are 40% for the landowner and 60% for the caretaker. A problem arises during the fourth harvest when the landowner requests an equal division, but the caretaker disagrees, feeling that the new arrangement is unfair. Based on the fiqh muamalah analysis, the caretaker is entitled to a larger share of the income because they contribute more in terms of labor, which justifies a higher reward. Therefore, the implementation of income distribution in the cooperation between the landowner and the caretaker in the production of Gulo Onou is in accordance with fiqh muamalah and permissible in Islam, as it fulfills the principles of justice in the contract and profit-sharing.